Amino acid mutations in Ebola virus glycoprotein of the 2014 epidemic. Issue 6 (17th March 2015) - Giovanetti, Marta; Grifoni, Alba; Lo Presti, Alessandra; Cella, Eleonora; Montesano, Carla; Zehender, Gianguglielmo; Colizzi, Vittorio; Amicosante, Massimo; Ciccozzi, Massimo
<x xml:space="preserve">Abstract</x> Zaire Ebola virus (EBOV) is an enveloped non‐segmented negative strand RNA virus of 19 kb in length belonging to the family Filoviridae. The virus was isolated and identified in 1976 during the epidemic of hemorrhagic fever in Zaire. The most recent outbreak of EBOV among humans, was that occurred in the forested areas of south eastern Guinea, that began in February 2014 and is still ongoing. The recent Ebola outbreak, is affecting other countries in West Africa, in addiction to Guinea: Liberia, Nigeria, and Sierra Leone. In this article, a selective pressure analysis and homology modeling based on the G Glycoprotein (GP) sequences retrieved from public databases were used to investigate the genetic diversity and modification of antibody response in the recent outbreak of Ebola Virus. Structural and the evolutionary analysis underline the 2014 epidemic virus being under negative selective pressure does not change with respect to the old epidemic in terms of genome adaptation. J. Med. Virol. 87:893–898, 2015. © 2015 Wiley Periodicals, Inc.